Neglected determinants relative to social well-being: an evidence from empirical studies - Norizan, Abdul Ghani; Fadzli, Adam; Mohamad Fauzi, Abdul Latib (2020)
Social well-being is one of the aspects related to individuals’ health. But unfortunately, studies have not been focusing on relative determinants of social well-being. Therefore, this study aims to evaluate whether previously conducted empirical studies (from 2011 to 2019) have identified the influence of determinant factors on social well-being or not. As the issue of social well-being deterioration that occurs among people is the manifestation of related factors within communities particularly in Malaysia. Online databases such as Google Scholar, Sociological Abstracts, International Bibliography of Social Sciences, PsycINFO, Springer Link, Arts and Humanities, Science Direct, Sociological Index, and Scopus have utilized to explore determinants relative to social well-being. However, no study has examined the impact of these selected determinants on individuals’ social well-being in developed countries as well as in Malaysia. All selected determinants and individuals’ social well-being needs to be evaluating in future studies to improve the community’s social well-being for the sake of performance and economic growth by implementing the appropriate policies.